ANALISIS PENERAPAN ASAS - ASAS TATA RUANG PADA RENCANAN TATA RUANG WILAYAH (RTRW) KABUPATEN LEBAK TERHADAP KEGIATAN PERTAMBAGAN KAWASAN GUNUNG LIMAN DI TINJAU BERDASARKAN UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG - Sindy Nur Fitriyani; Lusi Risma Wardah; Ahmad Rayhan; Nurikah Nurikah (Publication of the International Journal and Academic Research, 2024)
The Lebak Regency spatial planning plan was prepared based on Lebak Regency Regional Regulation Number 2 of 2014 concerning the Lebak Regency Regional Spatial Plan for 2014-2034 with the aim of creating a highly competitive and sustainable Regency regional space based on agriculture, plantations, tourism and mining. To realize this, spatial planning is needed based on the principles of spatial planning contained in Article 2 of Law Number 26 of 2007 concerning Spatial Planning. The research method used is the normative juridical method. The normative juridical method is defined as research on statutory rules, both from the perspective of the statutory hierarchy (vertical) and the harmonious relationship of legislation (horizontal). The purpose of this writing is to find out how the application of spatial planning principles in the Lebak Regency Spatial Planning Plan for Mining Activities in the Mount Liman Area is Reviewed Based on Law Number 26 of 2007 concerning Spatial Planning. Based on the results of the discussion, it can be concluded that the regional government has attempted to control spatial planning and supervision of illegal gold mining in Lebak Regency. Regulations for mining activities in Lebak Regency Regional Regulation Number 2 of 2014 concerning Lebak Regency Spatial Planning for 2014-2034. Article 64 paragraph (5) letter c does not allow mining in protected areas. However, there is a discrepancy in the application of spatial planning principles in the 2014-2034 Lebak Regency Regional Spatial Plan, namely consisting of the principle of integration, the principle of harmony, harmony and balance, the principle of sustainability, the principle of efficiency and effectiveness as well as the principle of legal certainty and justice. This is due to the determination of the Cirinten sub-district area as a mining area.